Management Tool for Green Spaces: Case of Setif Urban Park - Bouzekri, Sara; Madani, Said (Future Science, 2024)
Excessive urbanization in cities around the world, including Algeria, gen-erates significant tensions on the natural environment. Setif, like all Alge-rian cities, is confronted with this phenomenon, having acquired a frag-mented, discontinuous urban fabric resulting in a contrasting urban land-scape, characterized by an uneven spatial distribution of green potential. The proportion of existing greenery remains insufficient for a steadily growing population. Despite the efforts made by local authorities to pre-serve and enhance these spaces, no assessment of the quality of green spaces has been provided for. The purpose of this study is to explore an innovative and effective approach to the sustainable management and continuous improvement of green spaces. It is an attempt to qualitatively measure the spaces making up the urban park and to follow a strategy for their management, preservation and enhancement, encouraging reflec-tion on the levers of action to be taken. We use the method of evaluating the quality of green spaces, through the application and development of the quality index. This tool makes it possible to assess the sensitivity of the urban park to possible constraints and to value its strength factors. The quality index could serve as a model measurement tool for other cit-ies facing similar challenges. By exploring a management strategy based on the results of this index, city officials could identify elements requiring improvement and develop specific policies and initiatives to address the challenges faced.